Financial information and management decisions: Impact of accounting policy on financial indicators of the firm - Gintaras Černius; Liucija Birškytė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
To be useful for decision-making accounting information needs to be of high quality. This article examines how tax accounting rules may impact the accuracy and reliability of the information contained in financial statements. The simulation model reveals that significant distortions occur in accounting information due to the choice of depreciation period and methods. Using as benchmark ratios calculated applying accounting policy recommended in Business Accounting Standards a significant divergence between ratios has been found. This finding implies that ratios calculated using accounting rules allowable for Corporate Income Tax calculation can provide misleading information and lead to unsound financial management decisions.
Keywords: M41; M49; L20; 650; accounting; financial indicators; depreciation; long-term assets; management decisions; financial statements